A comparative study between direct safety trocar insertion versus veress needle technique for creating pneumoperitoneum in laparoscopic surgeries - Datey, Ashirwad; Jain, Satyendra; Patel, Rahul (International Surgery Journal, 2021)
Background: There are two methods of trocar insertion in laparoscopic surgeries one is direct insertion and second is Veress needle insertion. In this study we compared these two methods. Methods: In this study we divided 50 patients equally into two group group A for in group A patients, direct trocar insertion technique was used for creation of pneumoperitoneum whereas amongst patients of group B, pneumoperitoneum was created using Veress needle insertion technique. Results: The incidence of visceral injuries, vascular injuries and other post-operative complications were similar in both the groups. The present study observed no significant difference in failure rates between two methods. Conclusions: Both the techniques i.e.; Direct trocar insertion (DTI) and Veress needle technique are equally effective, safe and feasible for creation of pneumoperitoneum during laparoscopic procedure.